2012
DOI: 10.1245/s10434-012-2500-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Bleeding Complications after Gastric Cancer Surgery in Patients Receiving Anticoagulation and/or Antiplatelet Agents

Abstract: Perioperative antithrombotic treatment is an independent risk factor of postoperative bleeding complications in patients with gastric cancer undergoing radical gastrectomy, although such treatment was effective in preventing postoperative thromboembolic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…The risk of nonfatal postoperative major bleeding secondary to chemoprophylaxis is a matter of debate, with several studies reporting conflicting results. 1,2629 Mita et al 30 reported a higher rate of postoperative bleeding after gastric cancer surgery among patients receiving chemoprophylaxis (8.1 %) compared with no chemoprophylaxis (0.7 %). In contrast, Reddy et al 14 reported that VTE chemoprophylaxis did not increase the rate of red blood cell transfusion after major hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of nonfatal postoperative major bleeding secondary to chemoprophylaxis is a matter of debate, with several studies reporting conflicting results. 1,2629 Mita et al 30 reported a higher rate of postoperative bleeding after gastric cancer surgery among patients receiving chemoprophylaxis (8.1 %) compared with no chemoprophylaxis (0.7 %). In contrast, Reddy et al 14 reported that VTE chemoprophylaxis did not increase the rate of red blood cell transfusion after major hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Bulky bleeding is a wasting complication and is specific related to extended or super extended lymphadenectomy and may occurs in 0.6-3.6% (30). Luminal bleeding often originates from anastomosis sites and will not need any aggressive therapy.…”
Section: Hemorrhagementioning
confidence: 99%
“…The risk of developing hemorrhagic complications during or after surgery in patients with ATT remains uncertain. While several studies have reported the increasing risk of perioperative hemorrhagic complications with ATT [1][2][3], the safety and feasibility of surgery for patients with continuous aspirin therapy have also been reported recently in two randomized clinical trials regarding non-cardiac surgery [4,5] and several retrospective studies regarding abdominal surgery [6][7][8]. Chassot et al [9] recommend continuing aspirin preoperatively when prescribed as secondary prevention or cardiovascular disease or stroke because the risk of cardiovascular events when withdrawing them is generally higher than the risk of surgical bleeding.…”
Section: Introductionmentioning
confidence: 99%